Barriers and facilitators to accessing stroke care services in Tanzania: an explorative qualitative study among stroke survivors, caregivers and healthcare providers - Nyagwaswa Athanas Michael; Lilian Teddy Mselle; Costansia Anselim Bureta; Dickson Ally Mkoka; Yingjuan Cao (BMC Health Services Research)
Abstract Background Stroke is a leading cause of death and disability globally, posing a significant burden in low- and middle-income countries where universal access to healthcare services is limited. To improve access to stroke care services, the government of Tanzania has initiated public health campaigns to raise stroke awareness and established acute stroke units in tertiary hospitals. Nevertheless, lack of universal health coverage remains a significant obstacle to delivering high-quality healthcare services. Therefore, to enhance understanding of the factors influencing access to healthcare services amid the growing stroke burden, this study aims to explore barriers and facilitators to accessing stroke care services across the continuum of care in Tanzania. Methods The study adopted a descriptive phenomenology design and included 45 purposively recruited healthcare providers, stroke survivors and care givers at Muhimbili National Hospital-Mloganzila (MNH-Mloganzila) in Tanzania. In-depth interviews (IDIs) were conducted from June to September, 2024. Inductive thematic analysis was performed using Dedoose software. The study was approved by the Institutional Review Board of Muhimbili University of Health and Allied Sciences (Ref. No. MUHAS-REC-04-2024-2139). Results Thematic analysis revealed four barriers and three facilitators to accessing stroke care services across the continuum of care. The barriers to accessing stroke care services included low health literacy among stroke survivors and caregivers; high costs related to stroke care services, medical insurances and transport; inadequacy of essential healthcare resources at the lower-level healthcare facilities; and limitations in care processes at the national stroke center. The facilitators to accessing stroke care services included presence of strong social support systems; improved stroke service delivery at the national hospital; and increased funding allocation for healthcare training and service delivery. Conclusions To ensure equitable access to stroke care services across the continuum of care in Tanzania, the barriers identified must be addressed. The study underscores the importance of raising public awareness on stroke symptoms, and increasing availability of thrombolytic therapy, ambulance services, stroke diagnostics, physiotherapy centers, and stroke experts especially in regional referral hospitals in Tanzania.